Kinetics of Solidification and Crystallization of Liquid Axial Zone of Fe-C Alloys in Cylindrical Molds - V. Khrychikov; O. Semenov; Y. Aftandiliants; S. Gnyloskurenko; T. Semenova; H. Meniailo (Archives of Foundry Engineering)
According to the results of digitization of the experimental studies carried out in the past concerning Fe-C alloys solidification in cylindrical molds of castings with a carbon content of 0.04%, 0.1%, 0.4%, 0.93%, 1.42%; 2.44%, 3.28%, 4.45%, 4.83% and their subsequent interpolation in the range of 0.04 ÷4.83% С there were obtained the curves of the advancement of the pour point, liquidus and solidus in the coordinates of the relative thickness of the solidified metal layer x/R and the parametric criterion τ/R2. Their usage is proposed for the development of modes of physical and chemical influence on the liquid metal in the axial zone of the casting after solidification of its calculated layer. Calculation of the mass of modifiers or deoxidizers for introduction into the axial zone was performed in relation to the total mass of metal in the liquid and liquid-solid zones of the casting. The technique for calculating the mass and time of introduction a graphitizing modifier into the axial zone of rolling rolls made of hypereutectoid steel with 1.7% C is proposed to reduce the negative impact of cementite, chromium and molybdenum carbides on the structure of the axial zone of the rolls. The obtained curves can also be used to assess the accuracy of computer modeling of the processes of Fe-C alloys solidification and further adaptation of mathematical models by the correction of thermophysical coefficients, the values of which are not always known in the liquidus-solidus temperature range.